Consumer quality preferences: Parameters to accelerate bell pepper imaging and classification technology - Lazo Christian Joel; Jerusalem Emmanuel; Conejos Gabriel Angelo; Malabanan John Ace; Gallego Marianito (BIO Web of Conferences)
Marketability of fresh produce is highly dependent on consumer preferences. When consumers’ standards are not met, this will lead to food wastage in the long run. Manual sorting should be replaced with IoT technology that can classify fresh products based on different parameters. However, it is a difficult task and can sometimes be inaccurate. In this study, the authors aim to (1) understand the key quality parameters of bell pepper, (2) establish quality control measures from planting to consuming, and (3) understand and determine the technology features and parameters in terms of hardware preference and characteristics. The study gathered three groups of respondents namely the farmers, retailers, and household consumers. The paper concludes consumer preferences within the bell pepper industry and underscores the necessity of quality control measures to uphold standards and minimize losses such as temperature-controlled storage and sorting processes through computer vision.